Exchange Rate And Asean Share Price: An Analysis Of Asimmetry Response - Yanuar, Nyoman Suprastha, (Jurnal Manajemen, 2019)
The purpose of this study is to examine whether these markets react differently to market upturns and market downturns of markets using VAR models. This study Ã¯Â¬Ânds that following:. First, in line with many studies on international interdependencies of equity prices,. Second, the evidence strongly suggests significant responses of the ASEAN markets to the US exchange rate downturns Third, the pattern of responses based on impulse response functions further substantiate asymmetric responses of these markets to positive and negative shocks in the US exchange rate. Practical implications, suggest that the benefits of international portfolio diversification. The originality ofÃ‚Â  study is Ã‚Â exchange rates US have an impact on ASEAN stock market integration.